The Influence of Sit-Up and Squat-Jump Practice on Football Leading Results in Class VIII Students of SMP Negeri 8 Watampone - Muzakkir; Andi Ogo Darminto; Umrah Bahar; Adli Azhari (MultiTech Publisher, 2023)
The purpose of this study was to find out the effect of sit-up and squat-jump exercises on the results of heading soccer games for class VIII male students of SMP Negeri 8 Watampone. This research was a quasi-experimental study with a